Study of Electrocardiographic and Echocardiographic Findings for the Diagnosis of Left Ventricular Hypertrophy in Hypertensive Patients - Gupta, Piyush; Shahi, Aakash (Asian Journal of Medical Research, 2019)
Background: LVH is a common feature of hypertension and an ominous harbinger of cardiovascular sequelae. Most patients with hypertension, the heart becomes secondarily involved in response to the progressively increasing LV afterload. Compared with values in the normotensive group, LV mass index, LV wall thickness, and prevalence of LVH were markedly increased not only in untreated hypertensive patients but also in treated hypertensive with inadequate BP control which are poor markers of cardiovascular events. So this study was to identify the left ventricular hypertrophy using Sokolow- lyon and Romhilt estes and total QRS criteria in hypertensive patients, compare and correlate the efficacy of ECG to determine LVH in comparison to ECHO keeping ECHO as end point. Subjects and Methods: This was a cross-sectional observational study comparing ECG and ECHO in 100 patients diagnosed as hypertensive attending the outpatient in Department of Medicine or were admitted in the Medicine wards, Coronary Care units of Universal College of Medical College Teaching hospital, Bhairahawa for a period of 1 year from March 2014 to March 2015 were taken for study. Results: Our study shows Sokolow-Lyon criteria has sensitivity of 65% and specificity of 70% while Romhilt-Estes scoring system has a sensitivity of 70 % and a specificity of 73% and Total QRS criteria has sensitivity of 70% and specificity of 76%.Among the different criteria used, total QRS criteria showed better sensitivity and specificity compared to others in the present study Conclusion: ECHO facilities are not available in all rural regions, improved ECG criteria such as total QRS voltage can be recommended as a routine investigation for LVH because of its cost-effectiveness and easy availability despite certain limitations.